ANALISIS KEMAMPUAN SISWA BERKEBUTUHAN KHUSUS TUNARUNGU DALAM MEMECAHKAN MASALAH KONTEKSTUAL TOPIK BILANGAN BULAT [ANALYSIS OF DEAF STUDENTS’ ABILITY TO SOLVE CONTEXTUAL PROBLEMS ON INTEGER TOPICS] - Lidiana Fitria Ningsih; Halimatus Sakdiyah; Ulfa Masamah (JOHME: Journal of Holistic Mathematics Education, 2026)
This study aims to analyze the ability of deaf students to solve mathematical word problems on integer topics, particularly addition and subtraction operations. The study employed a descriptive qualitative approach involving two deaf junior high school students from a special education school in Batu City. Data were collected through problem-solving ability tests, interviews, observations, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, and was further examined based on Polya’s four stages of problem solving. The findings revealed that deaf students experienced difficulties in the stages of understanding the problem and devising a plan, especially in interpreting word problems related to integer operations. However, during the stages of carrying out the plan and reviewing the solution, the students were able to perform calculations accurately. Therefore, mathematics instruction for deaf students should incorporate visual aids, simplified language explanations, and contextual word problem exercises to enhance students’ understanding in the early stages of problem solving. BAHASA INDONESIA ABSTRACT: Penelitian ini bertujuan untuk menganalisis kemampuan siswa tunarungu dalam menyelesaikan soal cerita matematika pada materi bilangan bulat, khususnya operasi penjumlahan dan pengurangan. Penelitian menggunakan pendekatan kualitatif deskriptif dengan subjek dua siswa tunarungu tingkat SMP di salah satu sekolah luar biasa di Kota Batu. Data diperoleh melalui tes kemampuan pemecahan masalah, wawancara, observasi, dan dokumentasi. Analisis data dilakukan dengan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan, serta dikaitkan dengan empat tahapan pemecahan masalah Polya. Hasil penelitian menunjukkan bahwa siswa tunarungu mengalami kesulitan pada tahap memahami masalah dan merencanakan penyelesaian, terutama dalam menafsirkan kalimat soal yang berkaitan dengan operasi bilangan bulat, sedangkan pada tahap melaksanakan rencana dan memeriksa kembali siswa mampu melakukan perhitungan dengan baik. Oleh karena itu, pembelajaran matematika bagi siswa tunarungu perlu menggunakan bantuan visual, penjelasan bahasa yang sederhana, dan latihan soal cerita kontekstual untuk meningkatkan pemahaman pada tahap awal pemecahan masalah.